2016
DOI: 10.1016/j.jval.2016.08.616
|View full text |Cite
|
Sign up to set email alerts
|

Construction of System Dynamics Model for Medical Care System of Japan

Abstract: discrete choice data was used. The comparison between the models was performed using the criteria of logical consistency, goodness of fit, and parsimony. Results: From 1056 participants who completed the interview, 2 met criteria that excluded them from the primary analyses. The characteristics of remaining 1054 respondents were very similar to those of the Indonesian population. Descriptive analysis showed that anxiety/depression and pain/discomfort are the two dimensions with most reported health problems. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…And large hospitals provide inpatient services. 6) S. Inoue et al (2016) [5] conducted a study on Japan's hierarchical diagnosis system, which showed that community governments should also establish a more complete and strict management system for medical and health services. On the one hand, we must prevent the waste of medical expenses, so as to ensure the full and rational use of primary health resources.…”
Section: A Backgroundmentioning
confidence: 99%
“…And large hospitals provide inpatient services. 6) S. Inoue et al (2016) [5] conducted a study on Japan's hierarchical diagnosis system, which showed that community governments should also establish a more complete and strict management system for medical and health services. On the one hand, we must prevent the waste of medical expenses, so as to ensure the full and rational use of primary health resources.…”
Section: A Backgroundmentioning
confidence: 99%